Implementation of i-Spring Suite to improve Darul Muta’alimin students’ learning for critical thinking skills in natural science - Edi Suresman; Fitri Febrianti; Ruswan Dallyono (LPMPP Universitas Negeri Yogyakarta, 2023)
Low critical thinking skills are a crucial problem in science learning. Meanwhile, the purpose of this research was to determine the effect of the i-Spring Suite 10 media on students’ critical thinking skills in natural science. The research method used a quasi-experimental with a limited population, namely 6th-grade students of SDS IT Darul Muta'alimin. The sample was selected using a purposive sampling technique so that there were two classes that were used as samples, namely 6th A grade with 20 students and 6th B grade with 20 students. 6th A grade as an experimental class and used interactive multimedia based on i-Spring Suite 10. Meanwhile, 6th B grade was the control class and used audiovisual-based multimedia. The research instrument used a test with multiple choices and explanation. Based on the results of statistical analysis, the results of t-observed were 2.89 and t-critical with a significance level of 5% (ɑ = 0.05) of 2.025. From these results, it was found that tobserved t critical. This study concludes that there is a significant effect of the interactive multimedia based on i-Spring Suite 10 on students’ critical thinking skills in natural science subjects.